PERILAKU HERDING DAN OVERCONFIDENCE: MENJELAJAHI PENGARUH MEDIA SOSIAL TERHADAP KEPUTUSAN INVESTASI GENERASI Z - Purnomo Sutirto Adi (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to examine the influence of behavioral biases including overconfidence, loss aversion, herding behavior, confirmation bias, and Fear of Missing Out (FOMO) as well as the roles of social media, influencers, and financial literacy on investment decisions among Generation Z in Indonesia. A qualitative approach was employed through in-depth interviews with five investors aged 18–25 who have experience investing in stocks and/or cryptocurrencies. Data were analyzed using thematic analysis to identify patterns and themes related to investment decision-making. The findings indicate that Generation Z’s investment decisions are more influenced by psychological and social factors than by rational analysis; herding behavior and FOMO drive impulsive actions, while overconfidence increases overestimation of personal analytical ability. Influencers and social media content reinforce biased risk perceptions, whereas financial literacy, although adequate regarding basic investment concepts, is insufficient to fully mitigate the effects of behavioral biases. These results highlight the dominant role of social media and psychological factors in shaping Generation Z’s investment decisions, suggesting the need for interventions such as financial education, information verification, portfolio diversification, and regulatory oversight of investment promotions. This study contributes to behavioral finance literature and provides practical guidance for enhancing the quality of investment decisions among young investors in the digital era. Keywords: Z, Investment Decisions, Behavioral Bias, Financial Literacy, Social Media